The Role of Information Workers' Self-Determination in Access to Information for the Hearing and Speech-Impaired - Kurniawan, Adhi; Rahmi (JPUA: Jurnal Perpustakaan Universitas Airlangga: Media Informasi dan Komunikasi Kepustakawanan, 2025)
Background of Study: Inclusive access and services of information for persons with disabilities are an absolute necessity that must be provided by information institutions and supported by information workers and policies. Purpose: To determine the background, perceptions, and efforts of information workers in various information institutions to create inclusive information access and services for people with disabilities. Method: This study used a community-based learning approach with the self-determination theory method, which was deemed appropriate in exploring the background of information workers in providing inclusive access and services for people with disabilities, especially hearing and speech-impaired. Findings: Information workers have a general awareness of providing information services and access to deaf-mute people with disabilities. In its development, motivation and institutional support play a major role in the success of ideas and concepts of inclusiveness in information access and services. However, it was also found that the initiative of information workers emerged before access and service policies were created. Conclusion: Information workers hold vital roles in both creating support and policies for inclusive access and services for people with disabilities. The background and efforts that drive this inclusivity stem from the efforts and endeavors of information workers to understand, create, and implement inclusivity into concrete projections and relevant policies. Keywords: self-determination, information workers, information access, deaf disability, digital inclusion ---------------------------------------------------------------------------------------------------------------------------------------------------------------------- Peran Self-Determination Pekerja Informasi dalam Akses Informasi bagi Disabilitas Rungu-Wicara Latar Belakang: Akses dan layanan informasi yang inklusif untuk kelompok disabilitas merupakan upaya mutlak yang perlu disediakan lembaga informasi dan didukung oleh pekerja informasi serta kebijakan yang menyertainya. Tujuan: Mengetahui latar belakang, persepsi, dan upaya pekerja informasi dalam berbagai macam lembaga informasi untuk menciptakan akses dan layanan informasi yang inklusif kepada kelompok disabilitas. Metode: Penelitian ini menggunakan pendekatan community-based learning dengan metode self-determination theory yang dinilai sesuai dalam upaya penelusuran latar belakang pekerja informasi dalam memberikan akses dan layanan inklusif untuk kelompok disabilitias. Temuan: Pekerja informasi memiliki kesadaran umum dalam memberikan layanan dan akses informasi kepada kelompok disabilitas tuna rungu-wicara. Dalam perkembangannya, motivasi dan dukungan institusi memiliki peran besar dalam kesuksesan ide dan gagasan inklusivitas akses informasi dan layanan. Namun, juga ditemukan bahwa inisiasi pekerja informasi lebih dahulu muncul sebelum kebijakan akses dan layanan diciptakan. Kesimpulan: Pekerja informasi memiliki peran vital dalam menciptakan dukungan dan kebijakan akses dan layanan inklusif untuk kelompok disabilitas. Latar belakang dan upaya yang mendorong inklusivitas tersebut ditimbulkan dari upaya dan usaha pekerja informasi dalam memahami, menciptakan, dan mengimplementasi inklusivitas ke dalam proyeksi nyata dan kebijakan yang relevan.  Kata Kunci: self-determination, pekerja informasi, akses informasi, disabilitas rungu, inklusi digital